Antiglycemic and antihypertension potential of extract from Syzygium malaccense (L.) Merr. & L.M.Perry leaf - Thanh, Tran Huu; Huong, Nguyen Thi Mai; Diem, Nguyen Tran Kieu; Linh, Tran Le Phuong; Nguyen Kim Oanh,; Hoanh, Nguyen Dang; Thanh, Ha Quang; Phong, Bui Thanh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Diabetes and hypertension are diseases of an increased rate in humans. The target enzymes of two diseases are α-glucosidase, α-amylase, dipeptidyl peptidase-IV (DPP-IV), and angiotensin-converting enzyme (ACE). Objective: The aim of this study is to determine the inhibition ability of inhibition ability α-glucosidase, α-amylase, dipeptidyl peptidase-IV (DPP-IV), and angiotensin-converting enzyme (ACE) of extract from S. malaccense leaves. Materials and method: S. malaccense leaves were extracted with 96% alcohol at a ratio of 1:25 (w/v) to obtain total extract (TP). A quantity of total extract was fractionated with ethyl ether, ethyl acetate, and n-butanol solvents to obtain ethyl ether extract (EE extract), ethyl acetate extract (EA extract), n-butanol (BU extract), and the remaining aqueous solution (WA extract). TP extract and fractionated extracts were determined for enzyme inhibitory activity. Results: BU extract has the most potent inhibitory activity on α-amylase enzymes with an IC50 value of 265.23 µg/mL. The ethyl acetate (EA) extract was found with the highest inhibitory activity on α-glucosidase, DPP-IV, and ACE activity at IC50 values of 107.34 µg/mL, 160.07 µg/mL, and 186.32 µg/mL, respectively. Conclusion: The research indicates that leaf extracts can be applied to support the treatment of hypertension and diabetes.